ANALISIS PELAPORAN KEUANGAN AKUNTANSI ZAKAT BERDASARKAN PSAK 109 (Studi Kasus pada Lembaga Inisiatif Zakat Indonesia ) - Afelia Badriyah Afifah; Amsah Hendri Doni (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This research aims to find out about IZI's financial reports. This research analyzes the conformity of the Indonesian Zakat Initiative institution's financial reports with PSAK 109. The results of this research show that the Indonesian Zakat Initiative Institute makes financial reports based on PSAK 109 which contains recognition, measurement, disclosure or presentation and reporting. The recording carried out by the Indonesian Zakat Initiative (IZI) comes from proof of receipt of funds from muzakki in the form of the Zakat Deposit Forum (FSZ). The recording system used by the Indonesian Zakat Initiative (IZI) is a cash basis recording system. So the Indonesian Zakat Initiative (IZI) in terms of recognition is in accordance with the treatment of PSAK 109 concerning zakat accounting. The implementation of PSAK 109 in financial reports has an impact on increasing accountability, and showing transparency in order to increase public trust in order to increase zakat receipts. The presentation of IZI's financial reports has been prepared based on PSAK 109 standards and disclosed to the public on the official IZI website. The reports issued can be accounted for. The reporting made by the Indonesian Zakat Initiative is based on PSAK 109, seen from the five reports made, namely the financial position report, fund changes report, changes in assets under management report, cash flow report and notes report on financial reports